Ղարաբաղի խանության միացումը Ռուսաստանին՝ ըստ Կովկասի հնագրական հանձնաժողովի վավերագրերի - Հովհաննիսյան, Էդուարդ («Նաիրի» հրատ.)
The military and political situation of the early 19th century in Karabakh and the Russian-Persian War of 1804–1813 have been reflected in the Acts of the Caucasian Archaeographic Commission. Many archival documents in the Acts provide important historical details about the annexation of the Karabakh Khanate to Russia and the steps taken by the Russian government to fulfil this purpose. Many of these documents are not only of significant historical importance but also contain undeniable evidence of misinterpretation of facts of the history of the Armenian Karabakh by Azarbajanian historians. Сложившиеся в Карабахе в начале 19-го века военно-политическая ситуация и русско-персидская война 1804-1813 гг. нашли от- ражение на страницах собрания “Акты Кавказской археографической комиссии (АКАК)”. Многочисленные архивные документы в “Актах” сообщают важные подробности присоединения Карабахского ханства к России и шагов, предпринятых российским правительством для достижения этой цели. Многие из этих документов имеют не только подчеркнутую историческую важность, но и содержат неоспоримые доказательства искажения азербайджанскими историками фактов истории армянского Карабаха.
Keywords: Պատմություն; Վավերագրեր; Ղարաբաղ